Effekter av styrmedel på fordonsgasmarknaden - Carlgren, Andrea (2022)
One third of Sweden’s greenhouse gas emissions originates from the transport sector, nearly exclusively from domestic road transport. To reach the goal of net zero emissions by 2045, biofuels are needed to complement the electrification of the vehicle fleet. For biogas to be competitive compared to its fossil alternatives, policy instruments are required. There are many instruments like these in place in Sweden, but to ensure that resources are spent effectively, continuous evaluations of the different policy instruments are needed. This case study compares the combination of different policy instruments between Sweden and a comparable country in relation to their respective development of the vehicle gas market. To identify the country that is suitable for the comparison, calculations of Mahalanobis distance were performed. Then, the differences in development of the two vehicle gas markets were established through a hypothesis testing and lastly an analysis of the different policy instrument mixtures were conducted. The results show that Finland is the most suitable country for the comparison, based on several variables related to the biomass potential and the propensity for introducing climate policy instruments. The Finnish biogas market is less developed than the Swedish one, mainly due to a drive for nuclear power and other biofuels. An increase in the percentage change of refueling stations as well as the number of gas vehicles can be seen in Finland between 2016 and 2017. This can be a consequence of the state-owned Gasum investing in refueling infrastructure. Furthermore, Sweden have been directing policy instruments toward increased usage of biogas in the transport sector for a long time and thereby allowing faith in a stable market such that market actors dare to invest in biogas production and upgrading facilities.